Efek Komposisi Biochar dan Pasir pada Media Tanam Hidroganik serta Dosis Vermikompos Terhadap Pertumbuhan dan Hasil Tanaman Selada Keriting (Lactuca sativa L.) - siti hartina; Nurhidayati Nurhidayati; Indiyah Murwani (Folium : Jurnal Ilmu Pertanian, 2019)
This study aims to determine the interaction of the composition of planting media and vermicompost dosage on the growth and yield of lettuce plants. This study is a pot experiment conducted by green house located on Jl. MT. Haryono, Dinoyo Subdistrict, Lowokwaru Subdistrict, Malang with a altitude of ± 550 meters above sea level, the average air temperature ranges from 20 °C - 28 °C, which starts in February to June 2019. The study uses experimental Randomized Block Design (RBD) arranged in factorial and consists of 2 factors. The first factor was the composition of the planting medium consisting of 2 levels, namely M1: Cocopit (55%), Biochar (15%), Sand (30%) and M2: Cocopit (55%), Biochar (30%), Sand (15%) The second factor is the vermicompost dose which consists of five types, namely V1: 50 gram / pot, V2: 100 gram / pot, V3: 150 gram / pot, V4: 200 gram / pot, and V5: 250 gram / pot. Based on the two factors, 10 treatments were obtained and each treatment was repeated 3 times with 5 plant samples per treatment, until a sample of 150 lettuce plants was obtained. The results showed that the composition of the planting medium gave growth and yield of different lettuce plants, where the composition of M1 planting media (cocopeat 55%, 15% biochar and 30% sand) gave the highest growth and yield of plants at the dosage application of 200-250 g / pot while the composition of M2 planting media (55% cocopeat, 30% biochar and 15% sand), gave the highest growth and yield at 150-250 g / pot vermicompost doses. This is caused by the influence of the composition of the planting medium and vermicompost dosage on the total fresh weight of plants, fresh weight of roots and fresh weight economically valuable curly lettuce M2V4 treatment (55% cocopeat growing media, 30% biochar and 15% sand, with vermicompost 200 gram / pot), M2V1 (planting media, 55% cocopeat, 15% biochar and 30% sand, with 50 gram vermicompost / pot dose) and M2V4 (planting media, 55% cocopeat, 30% biochar and 15% sand, with dosage 200 gram vermicompost / pot) with values of 66.06, 6.24 and 61.62 grams giving the highest results. Keywords: planting media composition, vermicompost dosage